Pola Komunikasi Interpersonal Kepala Madrasah dalam Meningkatkan Profesionalisme Guru di Madrasah Aliyah Hidayatul Mubtadiin Lampung Selatan - Ainun Hidayah; Nurul Hidayati Murtafiah; Nur Widiastuti (Journal on Education, 2023)
The purpose of this study was to determine the implementation of the communication between the Head of Madrasah and staff, teachers both orally and in writing in increasing teacher professionalism at Madrasah Aliyah Hidayatul Mubtadiin, Jatiagung District, South Lampung Regency. This research was conducted using a qualitative research approach. In carrying out this qualitative research how to build knowledge through understanding and discovery. The use of this qualitative research approach is carried out because it relates to the research process and understanding based on a methodology that investigates social phenomena and human problems. In this study, data sources were taken from observations, interviews, and documentation from parties related to this research. The results of the study show that the Madrasah Principal does communicate with the teachers orally and in writing at the Madrasah in increasing professionalism at Madrasah Aliyah Hidayatul Mubtadiin, Jatiagung District, South Lampung Regency. While the form of communication carried out by the head of the madrasa with the teachers orally and in writing by the madrasa through internal communication using two forms, first the head of the madrasa carries out downward communication, namely communication that comes from the head of the madrasa to the teachers. The two madrasa heads also carry out upward communication, namely communication that comes from teachers to madrasa heads both orally and in writing.